Palayagars as feudatories under the Nayaks of Madurai - Lalitha, P.M. (Chennai P.M. Lalitha, 2009)
Study region comprising most of modern-day Tamil Nadu, India.
Originally presented as the author$1 (Bs thesis (Ph. D.-- Madurai Kamaraj University, 1990).s
Includes bibliographical references (p. 260-264).
Includes appendix in Kannada, Sanskrit, Tamil, and Telugu.
Keywords: Nayak dynasty of Madurai, |d 1529-1739.; Feudalism -- History. -- India -- Tamil Nadu; Tamil Nadu (India) -- Kings and rulers